Local Bacteriophage Delivery for Treatment and Prevention of Bacterial Infections - Rotman, Stijn Gerard; Sumrall, Eric; Ziadlou, Reihane; Grijpma, Dirk W.; Richards, Robert Geoff; Eglin, David; Moriarty, Thomas Fintan (Frontiers in Microbiology, 2020)
As viruses with high specificity for their bacterial hosts, bacteriophages (phages) are an attractive means to eradicate bacteria, and their potential has been recognized by a broad range of industries. Against a background of increasing rates of antibiotic resistance in pathogenic bacteria, bacteriophages have received much attention as a possible 'last-resort' strategy to treat infections. The use of bacteriophages in human patients is limited by their sensitivity to acidic pH, enzymatic attack and short serum half-life. Loading phage within a biomaterial can shield the incorporated phage against many of these harmful environmental factors, and in addition, provide controlled release for prolonged therapeutic activity. In this review, we assess the different classes of biomaterials (i.e. biopolymers, synthetic polymers and ceramics) that have been used for phage delivery and describe the processing methodologies that are compatible with phage embedding or encapsulation. We also elaborate on the clinical or pre-clinical data generated using these materials. While a primary focus is placed on the application of phage-loaded materials for treatment of infection, we also include studies from other translatable fields such as food preservation and animal husbandry. Finally, we summarize the trends in the literature and identify barriers to the application of phage loaded biomaterials in the clinic.